Early rate of force development and maximal strength at different positions of the athletic shoulder test in baseball players - Ashworth, B.; Hank, M.; Khaiyat, O.; Coyles, G.; Fallon Verbruggen, F.; Zemkova, E.; Zahalka, F.; Maly, T. (Sports, 2025)
Background/Objectives: Peak force (PF) reflects maximal strength, while early rate of force development (RFD; 0-100 ms) indicates explosive neuromuscular output. The Athletic Shoulder (ASH) test is gaining popularity in overhead athlete profiling, but its use for assessing explosive strength in various shoulder positions is underexplored. This study compared PF and RFD at shoulder abductions of 180° (ASH-I), 135° (ASH-Y), and 90° (ASH-T) in baseball players.